Color Test and Screening of Alkaloid, Saponin Levels of Citrus Fruit Peel Eco-Enzyme (Citrus reticulata) Eco-enzyme Solution as a Candidate for Teat Dipping Solution in Dairy Cattle - Rizqan; Roza, Elly; Arief; Susanty, Hilda (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Teat dipping is the activity of dipping the nipples of dairy cattle into an antiseptic solution that serves to coat and protect the nipples of livestock from harmful bacterial contamination so as not to cause disease in dairy cattle. This study aimed to obtain preliminary information about the color and screening of alkaloid and saponin content in the eco-enzyme solution, which will later be used as one of the natural antiseptic candidates for teat dipping solution in dairy cattle. This research uses descriptive analysis with the parameters observed, namely color and screening of alkaloid and saponin content in eco-enzyme solutions that have been diluted previously with the following percentages: A: 30% eco-enzyme solution + 70% aquades, B: 60% eco-enzyme solution + 30% aquades, and C: 100% eco-enzyme solution. From the results, it was found that the color of eco-enzyme solution A (transparent yellow), B (transparent yellow), and C (intense yellow and translucent color) while the qualitative test obtained A: positive, B: positive, C: positive (alkaloid content); A: negative, B: positive, and C: positive (saponin content). The results of color tests and screening of alkaloid and saponin content showed that good results were obtained in 100% eco-enzyme solution (C), which can be used as a candidate for natural teat dipping solution in dairy cows.